Technological Innovation Cooperation in Mega Construction Projects: A Conceptual Framework - Qing’e Wang; Zhenxu Guo; Liying Pan; Yi Li (Buildings, 2024)
Due to the dynamic and complex nature of mega construction projects (MCPs), mega construction project risks (MCPRs) have significantly increased in recent years. Technological innovation cooperation (TIC) is accepted as an approach to solve these issues. However, considering the new technological innovation challenges, technological innovation risks (TIRs) have been identified as a limitation of TIC. This study aims to develop a conceptual framework to explain TIC for MCPs. It is based on a review of the literature, engineering practice, and logical reasoning. The conceptual framework describes the interaction between MCPRs and TIC. It points out that MCPRs drive technological innovation, and technological innovation objectives guide the TIC. TIC has a negative effect on solving TIRs, and TIRs positively affect MCPRs. Cooperation performance will mediate the relationship between TIC and MCPRs. The conceptual framework may provide a theoretical basis to guide future empirical studies that validate the relationship between MCPRs and TIC and puts forward reasonable suggestions for MCPs.